Sleep Monitoring of Children With Nocturnal Enuresis: A Narrative Review - Zhu, Binbin; Zou, Kun; He, Jianhua; Huang, Xueqin; Zhu, Weichao; Ahmad Harb, Ahmad Khaled; Wang, Jianhua; Luo, Aiping (Frontiers in Pediatrics, 2021)
The purpose of this article is to provide a succinct summary of the sleep monitoring efforts that have been used in nocturnal enuresis (NE), and an overview of the knowledge that has accrued. This is not intended to be a comprehensive review but rather is intended to highlight how Polysomnography (PSG), a common sleep detection tool, has contributed to our understanding of NE, as arousal disorder is considered to be one of the important mechanisms. The authors have organized this report by analysis and display of different ingredients of PSG, starting with comparing the EEG of controls and the enuretic children, then moving to the evaluation of respiratory patterns of NE and comorbid disease obstructive sleep apnea (OSA). In addition, the authors’ goal is to better understand the mechanism of NE by integrating various levels of sleep monitoring, those sleep-related clinical scale scores for NE are presented to date. Finally, we propose further research of NE to explore the microstructures alterations via PSG combined with EEG-fMRI or to use novel technology like portable device internet and deep learning strategy.